Cutaneous Manifestations of Hypothyroidism A Prospective Hospital based clinical study in Bangladesh - Kumar, Saha Bijoy; Shahin, Md Mahabubur Rahaman; Siddique, Md Rahmat Ullah (Community Based Medical Journal, 2017)
Normal functioning thyroid is much more important for healthy skin. The association thyroid disorders with cutaneous manifestations is complex. Various studies have revealed multitude of cutaneous changes (in skin, hair and nails) that occur in thyroid hormonal dysfunction, in both hyper and hypothyroid states. The present study was designed to ascertain the varied cutaneous manifestations of hypothyroidism. This is a case control hospital based clinical study conducted in the Department of Dermatology and Venereology, BSMMU, over a period of one year, from May 2010 to May 2011. Fifty diagnosed cases of hypothyroidism constituted the subject material for the study and additional 50 Euthyroid persons were taken as control who were evaluated for the presence of any cutaneous manifestation. There are 50 patients of hypothyroidism among which 6 male & 44 female. The most common cutaneous feature in patients with hypothyroidism was coarse, rough, dry skin followed by pallor of skin, with carotenemia in 52.75% of the patients, nail changes in 38.9% of the patients, diffuse hair loss in 33.3% of the patients, palmoplantar keratoderma in 33.3% of the patients, and loss of lateral third of the eyebrows in 22.2% of the patients. Myxedematous facies were seen in 12% of the hypothyroid patients in our study. The relation between hypothyroidism and skin have profound clinical importance in dermatological practice. CBMJ 2017 January: Vol. 06 No. 01 P: 24-27